Quality assurance of VMAT on flattened and flattening filter‐free accelerators using a high spatial resolution detector. Issue 6 (11th April 2020) - Matar, F. S.; Wilkinson, D.; Davis, J.; Biasi, G.; Causer, T.; Fuduli, I.; Brace, O.; Stansook, N.; Carolan, M.; Rosenfeld, A. B.; Petasecca, Marco
Abstract: Purpose: This study investigated the use of high spatial resolution solid‐state detectors (DUO and Octa) combined with an inclinometer for machine‐based quality assurance (QA) of Volumetric Modulated Arc Therapy (VMAT) with flattened and flattening filter‐free beams. Method: The proposed system was inserted in the accessory tray of the gantry head of a Varian 21iX Clinac and a Truebeam linear accelerator. Mutual dependence of the dose rate (DR) and gantry speed (GS) was assessed using the standard Varian customer acceptance plan (CAP). The multi‐leaf collimator (MLC) leaf speed was evaluated under static gantry conditions in directions parallel and orthogonal to gravity as well as under dynamic gantry conditions. Measurements were compared to machine log files. Results: DR and GS as a function of gantry angle were reconstructed using the DUO/inclinometer and in agreement to within 1% with the machine log files in the sectors of constant DR and GS. The MLC leaf speeds agreed with the nominal speeds and those extracted from the machine log files to within 0.03 cm s −1 . The effect of gravity on the leaf motion was only observed when the leaves traveled faster than the nominal maximum velocity stated by the vendor. Under dynamic gantry conditions, MLC leaf speeds ranging between 0.33 and 1.42 cm s −1 were evaluated. Comparing the average MLC leaf speeds with the machine log files found differences between 0.9% and 5.7%, with the largest discrepancy occurring under conditions of fastest leaf velocity, lowest DR and lowest detector signal. Conclusions: The investigation on the use of solid‐state detectors in combination with an inclinometer has demonstrated the capability to provide efficient and independent verification of DR, GS, and MLC leaf speed during dynamic VMAT delivery. Good agreement with machine log files suggests the detector/inclinometer system is a useful tool for machine‐specific VMAT QA.